PENGARUH EFEKTIVITAS TEKNOLOGI SISTEM INFORMASI AKUNTANSI PADA KINERJA INDIVIDU DENGAN BUDAYA ORGANISASI SEBAGAI PEMODERASI - Sugiartini, Ni Made; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
The study was conducted to determine the effect of accounting information systems technology effectiveness in the performance of the individual and the moderating influence of organizational culture in the relationship between the effectiveness of the accounting information system technology with individual performance . This study used a sampling method with proportional stratified sampling formula Slovin then get 77 respondents. This research was conducted at the Department of Klungkung regency consisting of 12 Department . Classical assumption test and the suitability of the model are met and processing data using regression analysis techniques moderation that results show the effectiveness of the accounting information system technology has a positive and significant impact on individual performance . However, the culture of the organization is not able to moderate the influence of the effectiveness of the accounting information system technology on the performance of individuals in the Department of Klungkung .
Keywords: effectiveness of accounting information systems technology, organizational culture, individual performance